Rudolf Dreikurs papers - Dreikurs, Rudolf, 1897-1972.; Dreikurs, Rudolf, 1897-1972
Correspondence, speeches, lectures, writings, notes, student notebooks, transcripts of counseling and therapy sessions, case studies from classroom situations, printed matter, photographs, and other papers reflecting Dreikurs's career as a social psychologist and practitioner of group approaches in counseling and therapy. Documents his private practice of psychiatry in Chicago, Ill.; role in creating Community Child Guidance Centers of Chicago; professorship of psychiatry at the Chicago Medical School, North Chicago, Ill.; directorship of the Alfred Adler Institute of Chicago, Chicago, Ill.; and editorship of the Individual Psychology Bulletin. Also documents his work as an author and lecturer. Correspondents include Alfred Adler, Victor E. Frankl, John Haynes Holmes, George Kelly, Abraham H. Maslow, J.L. Moreno, Hans J. Morgenthau, Carl R. Rogers, Carleton Washburne, and Sumner Welles.
Psychiatrist and educator.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adler, Alfred, -- 1870-1937 -- Correspondence; Frankl, Viktor E. -- 1905-1997 -- Correspondence; Holmes, John Haynes, -- 1879-1964 -- Correspondence; Kelly, George, -- 1905-1967 -- Correspondence; Maslow, Abraham H. -- Correspondence; Moreno, J. L. -- 1889-1974 -- Correspondence; Morgenthau, Hans J. -- 1904-1980 -- Correspondence; Rogers, Carl R. -- 1902-1987 -- Correspondence; Washburne, Carleton, -- 1889-1968 -- Correspondence; Welles, Sumner, -- 1892-1961 -- Correspondence; Alfred Adler Institute of Chicago; Chicago Medical School -- Faculty; Community Child Guidance Centers of Chicago; Individual psychology bulletin; Adlerian psychology; Child guidance clinics -- Illinois -- Chicago; Child psychology; Group counseling; Group psychotherapy; Psychology; Psychology -- Periodicals; Psychiatry; Psychiatry -- Practice -- Illinois -- Chicago; Social psychology; Educators; Psychiatrists